A porous silicon-carbon composite material, a preparation method and application thereof

CN122599401APending Publication Date: 2026-08-18LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610786191.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-08-18

AI Technical Summary

Technical Problem

[0008]综上所述,现有技术中尚缺少一种能够穿透并全覆盖多孔硅内部孔壁、兼具离子导通与柔性力学缓冲的钝化结构

Benefits of technology

本发明实施例提供的多孔硅碳复合材料,包括多孔硅碳基体、纳米纤维网状钝化层和碳包覆层。其中,作为多孔碳骨架的的多孔碳基体的外表面及内部孔隙壁上沉积有纳米硅层,为硅的体积膨胀预留了缓冲空间。纳米纤维网状钝化层由无机纳米纤维相互交织搭接构成三维网状结构,其包覆于多孔硅碳基体的外表面和/或分布于多孔硅碳基体的内部孔隙,从而对纳米硅层的外表面和内部孔壁形成较为完整的钝化保护,能有效阻止电解液渗入引起的副反应。同时,纤维之间的开放网络有利于锂离子的快速传输,而纤维网络的弹性扩张和柔性牵拉能力可吸收体积应变,避免了刚性包覆层容易脆性断裂的问题。碳包覆层包覆于多孔硅碳基体的外表面,且碳包覆层在多孔硅碳基体的外表面处构成多孔硅碳复合材料的最外层。碳包覆层进一步提高了材料的导电性,并有助于保持电极结构完整。因此,本发明提供的多孔硅碳复合材料较低的体积膨胀率和良好的首次库伦效率,能够满足下一代高能量密度锂离子电池的需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122599401A_ABST
    Figure CN122599401A_ABST
Patent Text Reader

Abstract

The embodiment of the present application relates to a kind of porous silicon-carbon composite material and its preparation method and application, the porous silicon-carbon composite material includes: porous silicon-carbon matrix, including as porous carbon matrix of porous carbon skeleton and the nano-silicon layer deposited on the outer surface and internal pore wall of porous carbon skeleton;Nano-fiber mesh passivation layer is the three-dimensional mesh structure that inorganic nano-fiber interweaves and overlaps each other;Nano-fiber mesh passivation layer is coated on the outer surface of porous silicon-carbon matrix, and / or in the internal pore of porous silicon-carbon matrix, to form passivation protection to nano-silicon layer;Carbon coating layer, coated on the outer surface of porous silicon-carbon matrix;Wherein, carbon coating layer at the outer surface of porous silicon-carbon matrix constitutes the outermost layer of porous silicon-carbon composite material.The porous silicon-carbon composite material is applied to lithium ion battery negative electrode, with the characteristics of high initial coulomb efficiency, low expansion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery materials technology, and in particular to a porous silicon-carbon composite material, its preparation method, and its application. Background Technology

[0002] Silicon anode materials are considered core anode candidates for next-generation high-energy-density lithium-ion batteries due to their theoretical specific capacity of up to 4200 mAh / g (approximately 11 times that of graphite) and low lithium intercalation potential. However, silicon undergoes massive volume expansion and contraction exceeding 300% during charging and discharging, leading to particle breakage and pulverization, repeated rupture and regeneration of the solid electrolyte interphase (SEI) membrane, continuous consumption of active lithium and electrolyte, and problems such as extremely low cycle coulombic efficiency and rapid capacity decay.

[0003] To alleviate the aforementioned problems, porous structure designs have been widely adopted, reserving space for the volume expansion of silicon through internal pores. However, the pore size distribution of porous silicon ranges from a few nanometers to hundreds of nanometers, and it is mostly a tortuous and interconnected structure. As a highly reactive material, silicon's exposed inner and outer surfaces are prone to side reactions in electrolytes. Therefore, effective interfacial passivation of the inner and outer surfaces of porous silicon is a necessary prerequisite for ensuring its cycle stability. However, the unique pore geometry of porous silicon presents a fundamental challenge to this interfacial passivation process.

[0004] Currently, there are several technical approaches for interface passivation of porous silicon, but each has its own insurmountable drawbacks: First, a dense passivation layer technology based on vapor deposition.

[0005] This technology prepares an ultrathin metal oxide or carbon layer as a passivation layer on a silicon surface, following a layer-by-layer deposition pattern from the outside in. Within micron-level deep pores, this process is easily limited by Knudsen diffusion, leading to a sharp decrease in precursor concentration deep within the pores and resulting in a "thick outside, thin inside" coating morphology (excessively thick passivation layer on the outer surface, with no or discontinuous coverage on the inner pore walls). Electrolyte can still penetrate along the unpassivated pore walls, triggering continuous side reactions. Even if a dense layer is formed within the shallow pores through extremely extended deposition time, its dense, non-porous structure forces lithium ions to diffuse through the entire passivation layer via solid-phase diffusion, creating extremely high interfacial resistance and severely degrading rate performance. This indicates that there is an irreconcilable contradiction between "coverage integrity" and "ion transport unimpeded" in traditional dense passivation layer technology.

[0006] Second, external rigid shell confinement technology.

[0007] This technology employs carbon coating or a rigid shell to construct a dense "confined shell" on the outer surface of silicon particles, aiming to suppress the overall expansion of silicon through physical constraint. However, this technology only acts on the outer surface of the particles, offering no constraint on the numerous internal pore walls. During lithium intercalation, the rigid outer shell bears enormous circumferential tensile stress, while the internal pore walls, lacking constraint, expand freely inwards, creating a mechanical mismatch of "tight on the outside, loose on the inside." Because the rigid shell lacks the ability to locally deform to buffer the micro-expansion of the pore walls, it is highly susceptible to shell cracking or pore collapse, which in turn accelerates electrode structure failure. Once the shell yields and cracks, it permanently loses its ability to maintain electrical contact with internal silicon fragments.

[0008] In summary, the existing technology lacks a passivation structure that can penetrate and fully cover the internal pore walls of porous silicon, while also providing ion conduction and flexible mechanical buffering. Overcoming the fundamental contradiction between achieving "full coverage within the pores" and "low impedance transmission," and between "physical constraints" and "flexible anti-expansion," is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0009] The purpose of this invention is to address the shortcomings of existing technologies by providing a porous silicon-carbon composite material, its preparation method, and its application. The porous silicon-carbon composite material provided by this invention is used in the negative electrode of lithium-ion batteries and features high initial coulombic efficiency and low expansion rate. To achieve the above objectives, in a first aspect, the present invention provides a porous silicon-carbon composite material, the porous silicon-carbon composite material comprising: Porous silicon-carbon matrix, comprising a porous carbon matrix as a porous carbon framework and a nano-silicon layer deposited on the outer surface and internal pore walls of the porous carbon framework; The nanofiber mesh passivation layer is a three-dimensional mesh structure formed by the interlacing and overlapping of inorganic nanofibers. The nanofiber mesh passivation layer covers the outer surface of the porous silicon-carbon matrix and / or is distributed in the internal pores of the porous silicon-carbon matrix, adhering to the inner wall of the pores, thereby forming passivation protection for the nano-silicon layer. A carbon coating layer is applied to the outer surface of the porous silicon-carbon matrix; wherein the carbon coating layer forms the outermost layer of the porous silicon-carbon composite material on the outer surface of the porous silicon-carbon matrix.

[0010] Preferably, the porous carbon matrix includes one or more of the following: activated carbon, covalent organic framework materials, carbon fibers, graphene, graphene oxide, graphene-like materials with porous structures, or expanded graphite. The porous carbon matrix has a particle size D50 of 3μm-15μm and a specific surface area of ​​500m². 2 / g-2500m 2 / g, with a porous structure with pore sizes ranging from 1nm to 100nm inside.

[0011] Preferably, the thickness of the nano-silicon layer is 5nm-50nm, and its mass percentage in the porous silicon-carbon matrix is ​​30wt%-70wt%.

[0012] Preferably, the thickness of the nanofiber mesh passivation layer is 20nm-50nm.

[0013] Preferably, the porous silicon-carbon matrix contains pores with a diameter of 5nm-80nm to accommodate the end anchoring of the inorganic nanofibers and / or to provide buffer space for the volume expansion of silicon.

[0014] In a second aspect, the present invention provides a method for preparing the porous silicon-carbon composite material described in the first aspect above, the method comprising: A porous carbon matrix serving as a porous carbon framework is placed in a reactor and heated to the deposition temperature under a protective atmosphere. Then, a mixture of silicon source gas and inert carrier gas is introduced for chemical vapor deposition, depositing nano-silicon layers on the outer surface and internal pore walls of the porous carbon framework to obtain a porous silicon-carbon matrix. Under a protective atmosphere, the porous silicon-carbon matrix is ​​placed at a passivation temperature, and a mixture of inert carrier gas and passivation gas is introduced for chemical vapor deposition to form a passivation layer on the outer surface and / or internal pore walls of the porous silicon-carbon matrix, thereby obtaining a passivation material. Under a protective atmosphere, the passivation material is placed at a corrosion temperature, and a mixture of inert carrier gas and corrosive gas is introduced to perform a corrosion reaction on the passivation material, transforming the passivation layer into a nanofiber mesh passivation layer, thereby obtaining a porous silicon / carbon composite. The nanofiber mesh passivation layer is a three-dimensional mesh structure composed of interwoven inorganic nanofibers. The nanofiber mesh passivation layer coats the outer surface of the porous silicon-carbon matrix and / or is distributed within the internal pores of the porous silicon-carbon matrix, thus providing passivation protection for the nanosilicon layer. The porous silicon / carbon composite is subjected to carbon coating treatment to form a carbon coating layer on the outer surface of the porous silicon-carbon matrix, thereby obtaining a porous silicon-carbon composite material; wherein, the carbon coating layer constitutes the outermost layer of the porous silicon-carbon composite material on the outer surface of the porous silicon-carbon matrix.

[0015] Preferably, the porous carbon matrix includes one or more of the following: activated carbon, covalent organic framework materials, carbon fibers, graphene, graphene oxide, graphene-like materials with porous structures, or expanded graphite. The protective atmosphere and the inert carrier gas each comprise one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The silicon source gas includes one or more of silanes or chlorosilanes; The passivation gas includes one or more of aluminum isopropoxide, trimethylaluminum, tetra(dimethylamino)titanium, or titanium chloride. The corrosive gases include one or more of the following: carbon tetrafluoride, fluoromethane, sulfur hexafluoride, or nitrogen trifluoride.

[0016] Preferably, the deposition temperature is 300℃-700℃ and the deposition time is 3h-24h; The passivation temperature is 200℃-700℃, and the passivation time is 5min-200min; The corrosion temperature is 450℃-650℃, and the corrosion time is 1h-4h; When performing the carbon coating, the carbon coating temperature is 500℃-800℃ and the carbon coating time is 3h-12h.

[0017] Thirdly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising the porous silicon-carbon composite material described in the first aspect above, or comprising the porous silicon-carbon composite material prepared by the preparation method described in the second aspect above.

[0018] Fourthly, the present invention provides an energy storage device, the energy storage device comprising: for a lithium-ion battery or a lithium-ion capacitor; The energy storage device includes the porous silicon-carbon composite material described in the first aspect above, or the porous silicon-carbon composite material prepared by the preparation method described in the second aspect above, or the negative electrode sheet described in the third aspect above. The porous silicon-carbon composite material provided in this invention includes a porous silicon-carbon matrix, a nanofiber mesh passivation layer, and a carbon coating layer. The porous carbon matrix, serving as a porous carbon framework, has nanofiber silicon layers deposited on its outer surface and internal pore walls, providing a buffer space for silicon volume expansion. The nanofiber mesh passivation layer, composed of interwoven inorganic nanofibers forming a three-dimensional network structure, coats the outer surface of the porous silicon-carbon matrix and / or is distributed within its internal pores, thus providing relatively complete passivation protection for the outer surface and internal pore walls of the nanofiber layer, effectively preventing side reactions caused by electrolyte infiltration. Simultaneously, the open network between fibers facilitates rapid lithium-ion transport, while the elastic expansion and flexible tensile strength of the fiber network absorbs volumetric strain, avoiding the problem of brittle fracture easily caused by rigid coating layers. The carbon coating layer coats the outer surface of the porous silicon-carbon matrix, forming the outermost layer of the porous silicon-carbon composite material at this location. The carbon coating further improves the conductivity of the material and helps maintain the integrity of the electrode structure. Therefore, the porous silicon-carbon composite material provided by this invention has a low volume expansion rate and good first coulombic efficiency, which can meet the requirements of next-generation high-energy-density lithium-ion batteries. Attached Figure Description

[0019] Figure 1 A schematic diagram of the porous silicon-carbon composite material provided in the embodiments of the present invention. Figure 1 ; Figure 2 A schematic diagram of the porous silicon-carbon composite material provided in the embodiments of the present invention. Figure 2 ; Figure 3 A flowchart illustrating the preparation method of the porous silicon-carbon composite material provided by the present invention. Detailed Implementation

[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0021] The reagents and materials used in the following examples and comparative examples are all commercially available conventional reagent products, or can be prepared by conventional methods. Where specific experimental steps or conditions are not specified in the examples, they were performed according to conventional experimental steps and conditions in the art. Unless otherwise specified, all equipment used is conventional equipment currently available in the art.

[0022] First, it should be noted that in this application, the particle size D50 of the material refers to the median particle size of the material, which can be the median value sorted by volume, mass, or quantity. In the various embodiments of this invention, the median particle size sorted by quantity is specifically used, representing the particle size of the porous carbon matrix that accounts for 50% of the total number of particles. Particle size D50 is a well-known concept in the art. The particle size D50 of the material provided in the embodiments of this invention can be determined by instruments and conventional methods known in the art. Specifically, in the various embodiments of this invention, the particle size D50 is determined using a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0023] In this invention, the pore size of the porous carbon matrix refers to the diameter of the internal pores within the porous carbon matrix, a meaning known in the art. The pore size of the porous carbon matrix provided in the embodiments of this invention can be determined using instruments and conventional methods known in the art. Specifically, the Brunauer-Emmet-Teller (BET) gas adsorption method can be used, and the measuring instrument is a Micromeritics ASAP2460 specific surface area and pore size analyzer from McMuritics (Shanghai) Instruments Co., Ltd., USA.

[0024] This invention utilizes a nitrogen adsorption-desorption method and a specific surface area analyzer (model: BSD-660S) to measure the specific surface area.

[0025] Thickness testing method: The cross-section of the material was observed using a transmission electron microscope (accelerating voltage 200 kV). The thickness of the film was measured at 20 randomly selected locations, and the arithmetic mean was taken as the thickness value of the film. Among them, the thickness of the nano-silicon layer is the thickness of the silicon deposited layer on the outer surface and internal pore walls of the porous carbon framework; the thickness of the nanofiber mesh passivation layer is the radial distance from the outer surface of the silicon substrate to the outermost edge of the fiber network; and the thickness of the carbon coating layer is the coating thickness of the outermost carbon material.

[0026] This invention provides a porous silicon-carbon composite material, such as... Figure 1 and Figure 2 As shown, the porous silicon-carbon composite material comprises: Porous silicon-carbon matrix, including a porous carbon matrix as a porous carbon framework and a nano-silicon layer deposited on the outer surface and internal pore walls of the porous carbon framework.

[0027] The nanofiber mesh passivation layer is a three-dimensional mesh structure formed by the interweaving and overlapping of inorganic nanofibers. The nanofiber mesh passivation layer covers the outer surface of the porous silicon-carbon matrix and / or is distributed in the internal pores of the porous silicon-carbon matrix, thereby forming passivation protection for the nano-silicon layer.

[0028] A carbon coating layer is applied to the outer surface of the porous silicon-carbon matrix; wherein the carbon coating layer forms the outermost layer of the porous silicon-carbon composite material on the outer surface of the porous silicon-carbon matrix.

[0029] Preferably, the porous carbon matrix includes one or more of the following: activated carbon, covalent organic framework materials, carbon fibers, graphene, graphene oxide, graphene-like materials with porous structures, or expanded graphite.

[0030] Preferably, the porous carbon matrix has a particle size D50 of 3 μm-15 μm and a specific surface area of ​​500 m². 2 / g-2500m 2 / g, with an internal porous structure (such as micropores, mesopores and macropores) with a pore size of 1nm-100nm.

[0031] Preferably, the thickness of the nano-silicon layer is 5nm-50nm, and its mass percentage in the porous silicon-carbon matrix is ​​30wt%-70wt%.

[0032] Preferably, the thickness of the nanofiber mesh passivation layer is 20nm-50nm.

[0033] The porous silicon-carbon matrix contains pores with a diameter of 5nm-80nm, which serve to accommodate the end anchoring of inorganic nanofibers and / or provide buffer space for the volume expansion of silicon.

[0034] The porous silicon-carbon composite material provided in this invention includes a porous silicon-carbon matrix, a nanofiber mesh passivation layer, and a carbon coating layer. The porous carbon matrix, serving as a porous carbon framework, has nanofiber silicon layers deposited on its outer surface and internal pore walls, providing a buffer space for silicon volume expansion. The nanofiber mesh passivation layer, composed of interwoven inorganic nanofibers forming a three-dimensional network structure, coats the outer surface of the porous silicon-carbon matrix and / or is distributed on its internal pore walls, thus providing relatively complete passivation protection for the outer surface and internal pore walls of the nanofiber layer, effectively preventing side reactions caused by electrolyte penetration. Simultaneously, the open network between fibers facilitates rapid lithium-ion transport, while the elastic expansion and flexible tensile capabilities of the fiber network absorb volume strain, avoiding the problem of brittle fracture easily caused by rigid coating layers. The carbon coating layer coats the outer surface of the porous silicon-carbon matrix, forming the outermost layer of the porous silicon-carbon composite material at the outer surface of the matrix. The carbon coating further enhances the material's conductivity and helps maintain the integrity of the electrode structure. Therefore, the porous silicon-carbon composite material provided by this invention exhibits a low volume expansion rate and good first-time coulombic efficiency, meeting the requirements of next-generation high-energy-density lithium-ion batteries.

[0035] In addition, this invention also provides a method for preparing the above-mentioned porous silicon-carbon composite material, the main steps of which are as follows: Figure 3 As shown, the preparation method of porous silicon-carbon composite material includes: Step 110: The porous carbon matrix, which serves as a porous carbon framework, is placed in a reactor and heated to the deposition temperature under a protective atmosphere. Then, a mixture of silicon source gas and inert carrier gas is introduced to perform chemical vapor deposition, depositing nano-silicon layers on the outer surface and internal pore walls of the porous carbon framework to obtain a porous silicon-carbon matrix.

[0036] Specifically, a porous carbon matrix serving as a porous carbon framework is placed in a fluidized bed reactor and heated to a deposition temperature of 300℃-700℃ at a heating rate of 1℃ / min-10℃ / min under a protective atmosphere. After the temperature stabilizes, a mixture of silicon source gas and inert carrier gas is introduced for chemical vapor deposition (CVD) for 3-24 hours. The silicon source gas undergoes pyrolysis deposition on the outer surface and internal pore walls of the porous carbon framework, forming a nano-silicon layer to obtain a porous silicon-carbon matrix. After deposition, the silicon source gas is stopped, and inert gas is continuously introduced for 0.5-1 hour to remove unreacted gases and byproducts.

[0037] Through this step, a nano-silicon layer is uniformly deposited on the outer surface and internal pore walls of the porous carbon framework, forming a porous silicon-carbon matrix.

[0038] The porous carbon matrix can be selected from one or more of the following: activated carbon, covalent organic framework materials, carbon fibers, graphene, graphene oxide, graphene-like materials with porous structures, or expanded graphite. Activated carbon has a wide range of sources, including porous carbon materials obtained from biomass (such as coconut shells, fruit shells, wood chips, straw, etc.) after carbonization and activation treatment. The porous carbon matrix has a particle size D50 of 3μm-15μm and a specific surface area of ​​500m². 2 / g-2500m 2 / g, with an internal porous structure (such as micropores, mesopores and macropores) with a pore size of 1nm-100nm.

[0039] In the mixed gas consisting of silicon source gas and inert carrier gas, the volume concentration of silicon source gas is controlled at 10%-50%, and the total gas flow rate is 10L / min-30L / min.

[0040] The protective atmosphere and the inert carrier gas each include one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm.

[0041] The silicon source gas includes one or more of silanes or chlorosilanes (such as one or more of dichlorosilane, trichlorosilane or silicon tetrachloride).

[0042] Step 120: Under a protective atmosphere, the porous silicon-carbon substrate is placed at a passivation temperature, and a mixture of inert carrier gas and passivation gas is introduced for chemical vapor deposition to form a passivation layer on the outer surface and / or internal pore walls of the porous silicon-carbon substrate, thereby obtaining a passivation material.

[0043] Specifically, the porous silicon-carbon matrix obtained in step 110 is placed in a fluidized bed reactor and heated to the passivation temperature of 200℃-700℃ at a heating rate of 1℃ / min-10℃ / min under a protective atmosphere. After the temperature stabilizes, a mixture of passivation gas and inert carrier gas is introduced for chemical vapor deposition (CVD) for 1.5h-4h. The passivation gas is deposited on the outer surface and / or internal pore walls of the porous silicon-carbon matrix, forming a uniform and dense passivation layer, thus obtaining the passivated material. After deposition, the passivation gas is stopped, and inert gas is continuously introduced for purging for 0.5h-1h to remove unreacted gases and byproducts.

[0044] This step forms a dense passivation layer on the outer surface and / or internal pore walls of a porous silicon-carbon substrate, which serves as a precursor for subsequent corrosion.

[0045] Preferably, the passivation layer is a metal oxide; more preferably, it is one or more of aluminum oxide or titanium oxide. Therefore, the choice of passivation gas depends on the desired passivation layer. For example, when the passivation layer is aluminum oxide, the passivation gas can be one or more of aluminum isopropoxide or trimethylaluminum; when the passivation layer is titanium oxide, the passivation gas can be one or more of tetrakis(dimethylamino)titanium or titanium chloride. These passivation gases can be used in conjunction with a co-reactant (such as water vapor or oxygen). The volume ratio of the passivation gas to the inert carrier gas is 1:5-1:20, and the total flow rate is controlled at 0.5 L / min-6 L / min.

[0046] The protective atmosphere and the inert carrier gas include one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm.

[0047] Step 130: Under a protective atmosphere, the passivation material is placed at a corrosion temperature, and a mixture of inert carrier gas and corrosive gas is introduced to carry out a corrosion reaction on the passivation material, transforming the passivation layer into a nanofiber mesh passivation layer, thereby obtaining a porous silicon / carbon composite. The nanofiber mesh passivation layer is a three-dimensional mesh structure composed of interwoven inorganic nanofibers. The nanofiber mesh passivation layer covers the outer surface of the porous silicon-carbon matrix and / or is distributed in the internal pores of the porous silicon-carbon matrix, thereby forming passivation protection for the nanosilicon layer.

[0048] Specifically, the passivation material obtained in step 120 is placed in a fluidized bed reactor and heated to the corrosion temperature of 450℃-650℃ at a heating rate of 1℃ / min-10℃ / min under a protective atmosphere. After the temperature stabilizes, a mixture of corrosive gas and inert carrier gas is introduced, with a total gas flow rate of 10L / min-30L / min and a volume ratio of corrosive gas to inert carrier gas of 1:40-1:5, for a corrosion reaction of 1h-4h. During the corrosion process, the corrosive gas preferentially removes amorphous regions, defect-rich regions, or specific crystal plane micro-regions in the dense passivation layer, at least partially transforming the passivation layer into a three-dimensional network structure composed of interwoven inorganic nanofibers, i.e., a nanofiber network passivation layer. This nanofiber network passivation layer coats the outer surface of the porous silicon-carbon matrix and / or is distributed in the internal pores of the porous silicon-carbon matrix, adhering to the inner walls of the pores, thereby forming passivation protection for the nano-silicon layer. Preferably, the thickness of the nanofiber mesh passivation layer is 5nm-50nm, and more preferably, the thickness of the nanofiber mesh passivation layer is 20nm-50nm. After corrosion is completed, the corrosive gas is stopped, and inert gas is continuously introduced for 1-2 hours to remove residual corrosive gas and gaseous byproducts, thereby obtaining a porous silicon / carbon composite.

[0049] It should be noted that during the etching process, the corrosive gas preferentially removes specific micro-regions (such as amorphous regions, defect-rich regions, or specific crystal plane micro-regions) from the dense passivation layer. Simultaneously, fluorine-containing gas can also penetrate to the interface between the passivation layer and silicon, causing minor corrosion at the interface. This creates a small number of voids between the nanofibers and the silicon surface, providing additional buffer space for the volume expansion of silicon. Furthermore, as etching continues, the gas mass transfer path gradually becomes limited, automatically slowing the etching rate and preventing excessive etching that could lead to passivation layer peeling or excessive silicon loss.

[0050] This step transforms the dense passivation layer into a nanofiber mesh passivation layer, achieving passivation protection for the outer surface and / or internal pore walls of the porous silicon-carbon substrate.

[0051] Preferably, the protective atmosphere and the inert carrier gas each comprise one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm.

[0052] Preferably, the corrosive gas is a fluorine-containing corrosive gas, including one or more of carbon tetrafluoride, fluoromethane, sulfur hexafluoride, or nitrogen trifluoride.

[0053] Step 140: Carbon coating treatment is performed on the porous silicon / carbon composite to form a carbon coating layer on the outer surface of the porous silicon-carbon matrix, thereby obtaining a porous silicon-carbon composite material; wherein, the carbon coating layer constitutes the outermost layer of the porous silicon-carbon composite material on the outer surface of the porous silicon-carbon matrix.

[0054] Specifically, the porous silicon / carbon composite obtained in step 130 is transferred to a rotary kiln or fluidized bed reactor, and heated to a carbon coating temperature of 500℃-800℃ at a heating rate of 1℃ / min-10℃ / min under a protective atmosphere. After the temperature stabilizes, a mixture of carbon source gas and inert carrier gas is introduced, with a total gas flow rate of 5L / min-15L / min and a volume ratio of carbon source gas to inert carrier gas of 1:10-1:1, for carbon coating treatment for 3h-12h.

[0055] Carbon source gas is pyrolytically deposited on the outer surface of a porous silicon-carbon matrix to form a uniform carbon coating layer. After coating is completed, the carbon source gas supply is stopped, and the matrix is ​​allowed to cool naturally to room temperature under an inert atmosphere to obtain a porous silicon-carbon composite material.

[0056] This step forms a carbon coating layer on the outer surface of the porous silicon-carbon matrix, further improving the material's conductivity and structural integrity.

[0057] The carbon source gas includes one or more of methane, propane, or acetylene. The protective atmosphere and inert carrier gas include one or more of argon, nitrogen, or helium, wherein the oxygen content in the nitrogen is less than 5 ppm.

[0058] It should be further explained that the carbon coating process involves two scenarios: If steps 140 and 130 do not use the same equipment, then two carbon coating processes are required. The first carbon coating is performed in the same equipment as step 130. Its purpose is to form a protective layer on the surface of the porous silicon / carbon composite to prevent spontaneous combustion of the material due to exposed silicon caused by corrosion during the transfer to another equipment, thus improving production safety. Carbon coating is then performed again when the material is transferred to another equipment. Specifically, after the porous silicon / carbon composite is prepared in step 130, byproducts or unreacted gases generated during the preparation of the porous silicon / carbon composite are purged under a protective atmosphere. Then, the temperature is raised to the first coating temperature, and a mixture of inert carrier gas and carbon source gas is introduced for chemical vapor deposition to form a carbon coating layer on the outer surface of the porous silicon / carbon composite. After natural cooling, the material is removed and placed in another carbon coating device. Under a protective gas atmosphere, the temperature is raised to the second carbon coating temperature, and a mixture of inert carrier gas and carbon source gas is introduced for chemical vapor deposition to increase the thickness of the carbon coating layer.

[0059] The process parameters for the two carbon coating processes can be the same or different, depending on the actual needs.

[0060] If the same equipment is used in steps 140 and 130, carbon coating is performed once. The porous silicon / carbon composite is placed in the carbon coating equipment, heated to the carbon coating temperature under a protective gas atmosphere, and a mixture of inert carrier gas and carbon source gas is introduced for chemical vapor deposition to obtain the carbon coating layer.

[0061] Preferably, steps 140 and 130 do not use the same equipment and are performed twice for carbon coating.

[0062] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0063] Example 1 Step 1: Weigh 1 kg of commercially available biomass porous carbon and place it in a fluidized bed reactor. Using chemical vapor deposition (CVD), under nitrogen protection (flow rate 10 L / min), the reaction system is programmed to reach 500 °C at a heating rate of 5 °C / min and held at that temperature. Then, a mixture of silane and nitrogen is introduced for CVD for 300 min, with the total gas flow rate controlled at 20 L / min and the silane volume concentration at 30%. After deposition, the silane supply is stopped, and nitrogen is continuously purged for 0.5 h to obtain a porous silicon-carbon matrix. Step 2: Continue in the fluidized bed reactor, adjust the temperature to 200℃, continuously purge with nitrogen, turn on the vacuum system and purge with aluminum isopropoxide vapor as passivation gas, and simultaneously purge with water vapor as co-reactant, and perform in-situ gas phase passivation treatment for 2 hours, thereby forming a uniform and dense alumina passivation layer on the surface of the porous silicon carbon matrix material, and obtaining the passivated material.

[0064] Step 3: Continue heating the fluidized bed reactor to 500℃ under a nitrogen protective atmosphere. A mixture of sulfur hexafluoride (SF6) and nitrogen is introduced to corrode the passivation material for 2 hours. The volume ratio of SF6 to nitrogen is 1:24, i.e., the SF6 volume concentration is 4%. After corrosion, pure inert gas is introduced to purge for 2 hours to fully remove residual fluorine-containing gas and gaseous corrosion products from the equipment, resulting in a porous silicon / carbon composite.

[0065] Step 4: Continue to pass a mixture of acetylene and nitrogen gas at 500°C in the fluidized bed reactor at a volume ratio of 1:5 to perform a carbon coating on the above porous silicon / carbon composite. This provides a thin protective layer on the material surface, preventing the exposure of fresh silicon surfaces caused by corrosion from spontaneously combusting due to contact with air during material discharge. This improves production safety and yields a porous silicon-carbon semi-finished product.

[0066] Step 5: Remove the porous silicon-carbon semi-finished product and place it in a rotary kiln. Under nitrogen protection, heat it to 540℃ at a heating rate of 3℃ / min. Then, introduce a mixture of acetylene and nitrogen gas (total flow rate 8L / min, volume ratio 1:1) for carbon coating for 5 hours. After coating, allow it to cool naturally to room temperature under a nitrogen atmosphere to obtain the final porous silicon-carbon composite material.

[0067] Example 2 The difference between Example 2 and Example 1 is that the passivation layer in step 2 is titanium oxide, the passivation gas is titanium tetrachloride, and the passivation temperature is 200°C.

[0068] Example 3 The difference between Example 3 and Example 1 is that the passivation time in step 2 is 1.5 hours.

[0069] Example 4 The difference between Example 4 and Example 1 is that the passivation time in step 2 is 3 hours.

[0070] Example 5 The difference between Example 5 and Example 1 is that the corrosion time in step 2 is 4 hours.

[0071] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step 3, the etching treatment, is not performed.

[0072] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the passivation treatment in step 2 is not performed, nor is the treatment in step 3; only silicon deposition and carbon coating are performed.

[0073] The materials prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to the following tests: Electrochemical performance testing: The material was made into a negative electrode sheet, and then assembled into a coin cell using metallic lithium as the counter electrode for testing.

[0074] The above-mentioned silicon-carbon composite material (active material), conductive agent (Super P), and binder (sodium carboxymethyl cellulose and styrene-butadiene rubber in a 1:1 mass ratio) were added to an appropriate amount of deionized water at a mass ratio of 8:1:1. The mixture was then ground and slurried for 60 minutes until the slurry was homogeneous (solid content 40%-50%). The slurry was then uniformly coated onto a copper foil current collector (coating thickness 100μm-150μm). Subsequently, it was dried in a vacuum oven at 80℃ for 12 hours to remove the solvent. The dried electrode sheet was then cut into circular electrode sheets with a diameter of 12mm using a die-cutting machine, with a mass loading of 0.8 mg / cm². 2 -1.2mg / cm 2 A CR2032 coin cell was assembled in an argon-filled glove box (water and oxygen content both <1ppm). The electrolyte was 1mol / L lithium hexafluorophosphate (LiPF6), the solvent was ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1), the counter electrode was a lithium metal sheet, and the separator was Celgard 2400.

[0075] The CR2032 coin cell was left to stand for 8 hours at room temperature and then charged and discharged using a Blue Battery Testing System (CT2001A) at a rate of 0.1C. The lithium intercalation capacity and the 0.8V reversible capacity were recorded. The initial coulombic efficiency at 0.8V was calculated, and the results are recorded in Table 1. The initial coulombic efficiency at 0.8V is calculated as: (0.8V reversible capacity / lithium intercalation capacity) × 100%.

[0076] The coin cell expansion rate of the negative electrode was tested. The test method was as follows: At room temperature, the prepared negative electrode sheet was ion-beam cut, and the cross-section was photographed using a scanning electron microscope (SEM). The thickness of the negative electrode sheet before assembly into the coin cell was measured and recorded as T1; the thickness of the copper foil current collector substrate was measured and recorded as T2. Under a current density of 0.1C and a charging cutoff voltage of 2V, the coin cell was fully charged. Then, the battery was disassembled in a glove box, the negative electrode sheet was removed, and after ion-beam cutting, the cross-section was photographed using an SEM, and the thickness of the negative electrode sheet at this point was measured and recorded as T3. The coin cell expansion rate was then calculated using the formula: coin cell expansion rate = (T3 - T1) / (T1 - T2) × 100%, and the results are recorded in Table 1.

[0077] Table 1 As can be seen from the data comparison in Table 1, Examples 1-5 all successfully constructed nanofiber mesh passivation layers, and their volume expansion rate and first coulombic efficiency were better than those of Comparative Examples 1-2.

[0078] The expansion rate of Comparative Example 2 (without passivation and corrosion) was as high as 138.2%, but the initial coulombic efficiency was only 76.7%, indicating that the silicon volume expansion was completely uncontrolled and the side reactions were severe when there was no interface passivation layer.

[0079] The expansion rate of Comparative Example 1 (passivation only, no corrosion) was still as high as 108.5%. Although the initial coulombic efficiency was improved to 81.1%, it was still significantly lower than that of Examples 1-5. This indicates that although the passivation layer alone has a certain physical constraint, it cannot provide a built-in buffer space for volume changes due to its lack of its own pores and obstructed ion transport, resulting in a limited expansion suppression effect.

[0080] It is worth noting that the passivation layer thickness (20 nm) of Comparative Example 1 is similar to that of the nanofiber mesh passivation layer thickness (21 nm) in Example 3, but the expansion rate of Example 3 is significantly lower, further demonstrating that: without etching the passivation layer, a three-dimensional mesh structure cannot be formed, making it difficult to effectively provide ion transport channels and volume expansion buffer space.

[0081] A comparison of Examples 3 (passivation 1.5h, thickness 21nm), 1 (passivation 2h, thickness 36nm), and 4 (passivation 3h, thickness 42nm) shows that as the passivation time increases, the thickness of the nanofiber mesh passivation layer increases, the expansion rate gradually decreases, but the reversible capacity also decreases accordingly. This indicates that if the passivation time is too short, the coverage is incomplete, and the thickness of the formed passivation layer is too thin, which limits the thickness of the skeleton and the three-dimensional spatial extensibility of the mesh structure formed by subsequent transformation, resulting in insufficient expansion suppression effect; although a passivation time that is too long can further reduce the expansion rate, it will sacrifice capacity.

[0082] A comparison of Example 1 (etching for 2 hours) and Example 5 (etching for 4 hours) shows that extending the etching time further reduces the expansion rate from 82.5% to 76.2% while maintaining a high initial coulombic efficiency (84.7%), although the reversible capacity decreases slightly. This indicates that moderately extending the etching time is beneficial for more fully transforming the passivation layer into a nanofiber mesh passivation layer, forming a three-dimensional mesh structure, but excessive etching may lead to slight silicon loss and thickness reduction.

[0083] Furthermore, Example 2 (passivation layer is titanium oxide) has comparable performance to Example 1 (passivation layer is aluminum oxide), demonstrating that the present invention has good universality for passivation layer materials.

[0084] The above comparison fully demonstrates that only by synergistically combining the "passivation layer" and "vapor phase corrosion" can the passivation layer be transformed into a nanofiber mesh passivation layer, simultaneously achieving the triple functions of chemical passivation, rapid ion conduction, and adaptive volume expansion constraint. This invention successfully constructs a three-dimensional mesh structure anchored to the internal pore walls of a porous silicon-carbon matrix by corroding the passivation layer with fluorine-containing gas, effectively resolving the fundamental contradictions of existing technologies such as "incomplete coverage within the pores," "obstructed ion transport," and "easily broken rigid constraints."

[0085] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A porous silicon-carbon composite material, characterized by, The porous silicon-carbon composite material includes: Porous silicon-carbon matrix, comprising a porous carbon matrix as a porous carbon framework and a nano-silicon layer deposited on the outer surface and internal pore walls of the porous carbon framework; The nanofiber mesh passivation layer is a three-dimensional mesh structure formed by the interlacing and overlapping of inorganic nanofibers. The nanofiber mesh passivation layer covers the outer surface of the porous silicon-carbon matrix and / or is distributed in the internal pores of the porous silicon-carbon matrix, thereby forming passivation protection for the nano-silicon layer. A carbon coating layer is applied to the outer surface of the porous silicon-carbon matrix; the carbon coating layer forms the outermost layer of the porous silicon-carbon composite material on the outer surface of the porous silicon-carbon matrix.

2. The porous silicon-carbon composite material of claim 1, wherein, The porous carbon matrix includes one or more of the following: activated carbon, covalent organic framework materials, carbon fibers, graphene, graphene oxide, graphene-like materials with porous structures, or expanded graphite. The porous carbon base has a particle size D50 of 3-15 μm, a specific surface area of 500-2500 m 2 / g, and has a porous structure with a pore size of 1-100 nm inside. 2 / g, and has a porous structure with a pore size of 1-100 nm inside.

3. The porous silicon-carbon composite of claim 1, wherein, The thickness of the nano-silicon layer is 5nm-50nm, and its mass percentage in the porous silicon-carbon matrix is ​​30wt%-70wt%.

4. The porous silicon-carbon composite of claim 1, wherein, The thickness of the nanofiber mesh passivation layer is 20nm-50nm.

5. The porous silicon-carbon composite material according to claim 1, characterized in that, The porous silicon-carbon matrix contains pores with a diameter of 5nm-80nm, which are used to accommodate the end anchoring of the inorganic nanofibers and / or provide buffer space for the volume expansion of silicon.

6. A method for preparing the porous silicon-carbon composite material according to any one of claims 1-5, characterized in that, The preparation method includes: A porous carbon matrix serving as a porous carbon framework is placed in a reactor and heated to the deposition temperature under a protective atmosphere. Then, a mixture of silicon source gas and inert carrier gas is introduced for chemical vapor deposition, depositing nano-silicon layers on the outer surface and internal pore walls of the porous carbon framework to obtain a porous silicon-carbon matrix. Under a protective atmosphere, the porous silicon-carbon matrix is ​​placed at a passivation temperature, and a mixture of inert carrier gas and passivation gas is introduced for chemical vapor deposition to form a passivation layer on the outer surface and / or internal pore walls of the porous silicon-carbon matrix, thereby obtaining a passivation material. Under a protective atmosphere, the passivation material is placed at a corrosion temperature, and a mixture of inert carrier gas and corrosive gas is introduced to perform a corrosion reaction on the passivation material, transforming the passivation layer into a nanofiber mesh passivation layer, thereby obtaining a porous silicon / carbon composite. The nanofiber mesh passivation layer is a three-dimensional mesh structure composed of interwoven inorganic nanofibers. The nanofiber mesh passivation layer coats the outer surface of the porous silicon-carbon matrix and / or is distributed within the internal pores of the porous silicon-carbon matrix, thus providing passivation protection for the nanosilicon layer. The porous silicon / carbon composite is subjected to carbon coating treatment to form a carbon coating layer on the outer surface of the porous silicon-carbon matrix, thereby obtaining a porous silicon-carbon composite material; wherein, the carbon coating layer constitutes the outermost layer of the porous silicon-carbon composite material on the outer surface of the porous silicon-carbon matrix.

7. The preparation method according to claim 6, characterized in that, The porous carbon matrix includes one or more of the following: activated carbon, covalent organic framework materials, carbon fibers, graphene, graphene oxide, graphene-like materials with porous structures, or expanded graphite. The protective atmosphere and the inert carrier gas each comprise one or more of argon, nitrogen, or helium; wherein the oxygen content in the nitrogen is less than 5 ppm. The silicon source gas includes one or more of silanes or chlorosilanes; The passivation gas includes one or more of aluminum isopropoxide, trimethylaluminum, tetra(dimethylamino)titanium, or titanium chloride. The corrosive gases include one or more of the following: carbon tetrafluoride, fluoromethane, sulfur hexafluoride, or nitrogen trifluoride.

8. The preparation method according to claim 6, characterized in that, The deposition temperature is 300℃-700℃, and the deposition time is 3h-24h; The passivation temperature is 200℃-700℃, and the passivation time is 1.5h-4h; The corrosion temperature is 450℃-650℃, and the corrosion time is 1h-4h; When performing the carbon coating, the carbon coating temperature is 500℃-800℃ and the carbon coating time is 3h-12h.

9. A negative electrode sheet, characterized in that, The negative electrode sheet comprises the porous silicon-carbon composite material according to any one of claims 1-5, or the porous silicon-carbon composite material prepared by any one of claims 6-8.

10. An energy storage device, characterized in that, The energy storage device includes: for lithium-ion batteries or lithium-ion capacitors; The energy storage device includes the porous silicon-carbon composite material according to any one of claims 1-5, or the porous silicon-carbon composite material prepared by any one of claims 6-8, or the negative electrode sheet according to claim 9.